Congenital bilateral cataract in a newborn with Down syndrome (Archives of Pediatrics of Uruguay, 2022)
Cataracts are a major cause of visual impairment in the pediatric population worldwide and can significantly affect a child’s neurobiological development. Congenital cataract management can become a very important problem and is one of the most important causes of blindness in developed and developing countries. Trisomy 21 is the most common chromosomal disease and it has certain phenotypic characteristics and 60% ophthalmic abnormalities, such as, ametropia, keratoconus and cataracts. The diagnosis is fundamentally clinical. Early identification, diagnosis, and appropriate clinical care are key to achieve optimal results. We present the case of a newborn with Down syndrome who was diagnosed with an early bilateral congenital cataract.
Keywords: Bilateral cataract; Down Syndrome